Complex Networks - Erciyes, K (Guide to Graph Algorithms, 2018)
Complex networks consist of tens of thousands of nodes and hundreds of thousands of edges connecting these nodes. The graphs used to model these networks are large and special methods are commonly needed for the analysis of these networks. The main complex networks which are biological networks, social networks, technological networks and information networks are reviewed with brief description of the algorithms needed to solve some problems in these networks in this chapter.